Mercury Deposition, Climate Change and Anthropogenic Activities: A Review - Li, Feng; Ma, Chunmei; Zhang, Pingjiu (Frontiers in Earth Science, 2020)
As a toxic and harmful global pollutant, mercury enters the environment through natural sources, and human activities. Based on large numbers of previous studies, this paper summarized the characteristics of mercury deposition and the impacts of climate change and human activities on mercury deposition from a global perspective. The results indicated that global mercury deposition changed synchronously, with more accumulation during the glacial period and less accumulation during the interglacial period. Mercury deposition fluctuated greatly during the Early Holocene but was stable and low during the Mid-Holocene. During the Late Holocene, mercury deposition reached the highest value. An increase in precipitation promotes a rise in forest litterfall Hg deposition. Nevertheless, there is a paucity of research on the mechanisms of mercury deposition affected by long-term humidity changes. Mercury accumulation was relatively low before the Industrial Revolution ca. 1840, while after industrialization, intensive industrial activities produced large amounts of anthropogenic mercury emissions and the accumulation increased rapidly. Since the 1970s, the center of global mercury production has gradually shifted from Europe and North America to Asia. On the scale of hundreds of thousands of years, mercury accumulation was greater in cold periods and less in warm periods, reflecting exogenous dust inputs. On millennial timescales, the correspondence between mercury deposition and temperature is less significant, as the former is more closely related to volcanic eruption and human activities. However, there remains significant uncertainties such as non-uniform distribution of research sites, lack of mercury deposition reconstruction with a long timescale and sub-century resolution, and the unclear relationship between precipitation change and mercury accumulation.